Dampak Keberadaan Kawasan Industri Pelabuhan JIIPE Terhadap Penciptaan Lapangan Pekerjaan (Desa Karangrejo, Kabupaten Gresik) - Yoga Kinasi Gusti, yogakinasi15 (Program Studi Ekonomi Pembangunan, 2024)
This research aims to identify the profile of types of employment before and after the construction of the JIIPE industrial area, as well as the levels of education and types of jobs in relation to community income in Karangrejo Village, Manyar District, Gresik Regency. The research method used is quantitative with a multiple linear approach. Data for this study were obtained from various sources, including questionnaires and interviews. The variables used in the analysis include education level, job type, and income. The results of the study show that the education level variable (X1) has a positive and significant effect on community income. The job type variable (X2) also has a positive and significant effect on community income. Additionally, the education level and job type variables simultaneously have a significant effect on community income, as evidenced by a significance value of 0.000 < 0.05. Thus, the higher the education level of the community in Karangrejo Village, the higher their income. The emergence of the JIIPE Industrial Area in Karangrejo District benefits the surrounding community by increasing the number of available jobs in the area.